A novel cell-free intrathecal approach with PRP for the treatment of spinal cord multiple sclerosis in cats - Mariam F. Farid; Yara S. Abouelela; Noha A. E. Yasin; Mohamed R. Mousa; Marwa A. Ibrahim; Abdelbary Prince; Hamdy Rizk (BMC, 2022)
Abstract Background Multiple sclerosis (MS) is a progressive autoimmune demyelinating disease of the central nervous system. To date, there is no effective therapy for it. Our study aimed to determine the potential role of platelet-rich plasma (PRP) in the treatment of MS in cats. Methods The current study was conducted on 15 adult Persian cats that were divided into three groups: control negative, control positive (ethidium bromide (EB)-treated group), and PRP co-treated group (EB-treated group intrathecally injected with PRP on day 14 post-spinal cord injury). PRP was obtained by centrifuging blood on anticoagulant citrate dextrose and activating it with red and green laser diodes. The Basso-Beattie-Bresnahan (BBB) scores were used to assess the motor function recovery on days 1, 3, 7, 14, 20, and 28 following 14 days from EB injection. Moreover, magnetic resonance imaging (MRI) analysis, histopathological investigations, transmission electron microscopy (TEM) studies, and immunohistochemical analysis were conducted, and the gene expressions of nerve growth factors (NGFs), brain-derived neurotrophic factors (BDNF), and stromal cell-derived factors (SDF) were evaluated. Results Our results indicated that PRP had a significant ameliorative effect on the motor function of the hindlimbs as early as day 20 and so on. MRI revealed that the size and intensity of the lesion were significantly reduced in the PRP co-treated group. The histopathological and TEM investigations demonstrated that the PRP co-treated group had a significant improvement in the structure and organization of the white matter, as well as a high remyelination capacity. Furthermore, a significant increase in myelin basic protein and Olig2 immunoreactivity as well as a reduction in Bax and glial fibrillar acidic protein immune markers was observed. NGFs were found to be upregulated by gene expression. Conclusion As a result, we concluded that the intrathecal injection of PRP was an effective, safe, and promising method for the treatment of MS.